Enforcement of the Comprehensive Dangerous Drug Law: Implications to Supply and Demand Reduction - Bondoc, Meliza U. (Future Science / FSH-PH Publications, 2025)
This study assessed the enforcement of the comprehensive dangerous drug law in Carmona City, Province of Cavite, and its implications for the supply and demand reduction drive. A descriptive method of research was employed to conduct this study. The respondents were the police personnel assigned and the barangay captains of the different barangays within the study setting. The statistical tools used were frequency and percentage distribution, weighted mean, and the chi-square test. The level of significance was established at 0.05. The study's findings reveal that the enforcement of the Comprehensive Dangerous Drugs Act in Carmona City is largely effective, yet impeded by significant operational constraints; nonetheless, this effective enforcement positively impacts both supply and demand reduction efforts concerning dangerous drugs, underscoring the essential requirement for ongoing capacity-building, institutional support, and policy reinforcement to guarantee the sustained success of anti-drug initiatives in local communities.